Influence Of Work Life Balance And Work Environment On Employee Performance PDAM Tirta Bukae North Luwu - Pratiwi, Ananda; Saharuddin, Saharuddin; Patra, I Ketut (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to analyze the influence of work life balance and work environment on employee performance at PDAM Tirta Bukae, North Luwu. Methodology: This study employed a quantitative approach, with a population of 70 employees and a saturated sampling technique. Data collection was conducted using a questionnaire focusing on aspects of work-life balance, work environment, and employee performance. Data analysis was performed using multiple linear regression, validity tests, reliability tests, and hypothesis testing. Results and Findings: The results of the study indicate that both work-life balance and the work environment have a significant positive effect on employee performance. Work-life balance, which involves employees' ability to manage work responsibilities and personal life, has been shown to increase productivity and job satisfaction. A conducive work environment, including adequate facilities, effective communication, and supportive policies, also plays a significant role in improving employee performance. This study also confirmed that work-life balance and the work environment simultaneously influence employee performance by 78.7%. Novelty and Originality: This research brings novelty by shifting the focus from the private sector to the public service sector, namely PDAM Tirta Bukae Luwu Utara, which has different organizational characteristics, work culture, and managerial structure from private companies. Conclusion: This study concludes that Work Life Balance and work environment have a significant effect on the performance of PDAM Tirta Bukae North Luwu employees. A good Work Life Balance improves employee performance, as does a conducive work environment. Simultaneously, both variables play an important role in improving employee performance.Type of Paper: Empirical research article.